Soil Organic Carbon Pools as Early Indicators for Soil Organic Matter Stock Changes under Different Tillage Practices in Inland Pacific Northwest - Awale, Rakesh; Emeson, Micco A.; Machado, Stephen (Frontiers in Ecology and Evolution, 2017)
Soil organic matter (SOM) is essential for sustaining soil health and crop productivity. However, changes in SOM stocks in response to agronomic practices are slow and show years later when it is too late for adjustments in management. Identifying early indicators of SOM dynamics will allow early management decisions and quick remedial action. The objectives of this study were to evaluate long-term effects of tillage intensity and timing on SOM pools and determine the most responsive SOM pools to tillage practice. Soil from a long-term (53 yrs) winter wheat (Triticum aestivum L.) - spring pea (Pisum sativum L.) rotation and undisturbed grass pasture (GP) in inland Pacific Northwest (iPNW) was sampled to evaluate the effect of four tillage systems [no-till (NT), disk/chisel (DT/CT), spring plow (SP), and fall plow (FP)] on soil organic carbon (SOC, proxy for SOM), total nitrogen (TN), particulate organic matter carbon (POM-C) and nitrogen (POM-N), permanganate oxidizable carbon (POXC), water extractable organic carbon (WEOC), total dissolved nitrogen (TDN), KCl-extractable nitrogen (KEN), microbial biomass carbon (MBC) and nitrogen (MBN), basal respiration (BR), carbon mineralization (Cmin), and metabolic quotient (qCO2). GP had higher levels of SOC pools than cultivated treatments. On average, tillage significantly decreased SOC and TN by 28% and 26%, respectively, compared to GP. Among the cultivated soils, tillage had no significant effect on SOC and TN, except for DT/CT that had slightly higher SOC than FP (P=0.08). On the contrary, NT and DT/CT significantly (P<0.05) increased levels of POM-C, POM-N, POXC, WEOC, MBC, BR, Cmin, and qCO2 over FP or SP. However, tillage did not affect TDN, MBN, and KEN. The C-pools (POM-C, POXC, MBC, WEOC, BR, and Cmin) were more strongly correlated with SOM than the N-pools (TDN, MBN, and KEN), with an exception to POM-N. Under wheat-pea rotation in the iPNW, reduced tillage systems (NT and DT/CT) have a potential to maintain or increase SOM, which can be assessed early through its physical (POM), chemical (POXC, WEOC), and microbiological (MBC, BR, Cmin) indicators. POXC and WEOC were the most sensitive indicators of tillage-induced changes in SOM dynamics.